2006
DOI: 10.1063/1.2354584
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interaction of submicron-sized ferromagnetic rings in one-dimensional array

Abstract: Magnetization characteristics of submicron-sized ferromagnetic rings in a one-dimensional array with various inter-ring distances, l x , were investigated by the magneto-optical Kerr effect and micromagnetic simulation. The onion ͑vortex͒-to-vortex ͑onion͒ transition fields were found to be proportional to 1 / l x n with n = 1.36 ͑0.79͒, instead of being a simple dipole interaction model ͑n =3͒. It was demonstrated that the transition mechanism and the inter-ring dependence are governed by the energy gain orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
(5 reference statements)
2
10
0
1
Order By: Relevance
“…In this first calculation, we just calculate the components of the energy without minimization; we thus obtain the energy at a fixed value of local magnetic structure in the spheres, disregarding the polarization energy. The result is displayed in figure (8 (1, 2), and moreover the proportionality factor is exactly the result of the dipolar interaction, as deduced from (13). We thus conclude that when the structure inside the spheres is frozen, the resulting interaction energy is indeed given by the dipolar interaction between the vortex cores.…”
Section: Interaction Beween Particlessupporting
confidence: 68%
See 2 more Smart Citations
“…In this first calculation, we just calculate the components of the energy without minimization; we thus obtain the energy at a fixed value of local magnetic structure in the spheres, disregarding the polarization energy. The result is displayed in figure (8 (1, 2), and moreover the proportionality factor is exactly the result of the dipolar interaction, as deduced from (13). We thus conclude that when the structure inside the spheres is frozen, the resulting interaction energy is indeed given by the dipolar interaction between the vortex cores.…”
Section: Interaction Beween Particlessupporting
confidence: 68%
“…Then, we have to take into account two contributions. The first one which corresponds to (13), is nothing 1)) where H dip (r 12 )ĥ dip (2, 1) is the dipolar field created at r 1 by particle at r 2 and the second one is twice the polarization energy of each sphere in the field of the second one.…”
Section: Magnetization Structure and Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…For single domain particles, m i ¼ M s v s where M s is the saturation magnetization of the particles, and the orientationsm i result from the minimum of d 112 given in (5). For particles without magnetocrystalline anisotropy, this gives:m 1 ¼m 2 ¼r 12 and d 112 ¼ À2.…”
Section: Interaction Between Magnetic Nanospheresmentioning
confidence: 99%
“…5 The OS to VS transition was found to be highly dependent on the edge to edge distance of the rings. [12][13][14] It was shown that beyond a critical distance the magnetostatic interactions between adjacent elements become insignificant, leading to a radical change in the DW dynamics. In case of NiFe ring arrays, the observed critical distance was >100 nm.…”
Section: Introductionmentioning
confidence: 99%